El Aprendizaje Basado en Proyectos como Herramienta de Innovación Educativa: Lecciones de Dos Colegios en Bogotá (Memorias Sifored - Encuentros Educación UAN, 2023)
Innovating in the classroom entails the design and implementation of activities that spark students´ passion for learning. This is not an easy task because teachers are inundated with academic and administrative responsibilities, which leave them with little time for planning. Lack of tools to foster educational innovation in the classroom constitutes a daunting challenge in education. Consejo de Curso is a non-for-profit organization, based in Chile, and since 2014 has been working on the implementation of educational programs to close learning gaps using project-based learning methodologies. This study, qualitative in nature, aimed at understanding the extent to which project-based learning methodologies can nudge students´ interest and passion for learning. By conducting semi-structured interviews to the teachers who participated in the pilot project as well as by employing thematic and discourse analysis techniques, this study suggests that project-based learning facilitates students´ development of cognitive and non-cognitive skills (e.g., soft skills and social emotional skills).
Keywords: Educational innovations using CTI; Out of school education; Educational innovations; Teaching method innovations